2018
DOI: 10.1002/app.47400
|View full text |Cite
|
Sign up to set email alerts
|

Synergized poly(lactic acid)–hydroxyapatite composites: Biocompatibility study

Abstract: In vitro biocompatibility of impact modified composites produced from poly(lactic acid) (PLA) and hydroxyapatite (HA) is reported in this study. Surface modification was previously used to facilitate the dispersion of HA in PLA, whereas impact property of the PLA-HA composites was deliberately enhanced as it was necessary. Herein, osteoblast cell culture assay was used to assess the possible effects of HA surface modification and impact modification on the cell behavior in physiological media. Furthermore, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…However, it is noteworthy that improved interaction between PLA and GF following the incorporation of BS helped to shift the T m of the resulting ternary composite (PLA-GB) by about 4 C as presented in Table 4. Afterwards, a significant left shift in the T c can be seen in the PLA-GBC system which is an indication of increased nucleation activities in the composite, 39,40 accrued to the incorporation of CESA. Although similar observation was reported in a previous study where CESA was incorporated into PLA without any reinforcing filler, 30 it is interesting to note here that same effect can be achieved in reinforced PLA.…”
Section: Samplementioning
confidence: 96%
See 2 more Smart Citations
“…However, it is noteworthy that improved interaction between PLA and GF following the incorporation of BS helped to shift the T m of the resulting ternary composite (PLA-GB) by about 4 C as presented in Table 4. Afterwards, a significant left shift in the T c can be seen in the PLA-GBC system which is an indication of increased nucleation activities in the composite, 39,40 accrued to the incorporation of CESA. Although similar observation was reported in a previous study where CESA was incorporated into PLA without any reinforcing filler, 30 it is interesting to note here that same effect can be achieved in reinforced PLA.…”
Section: Samplementioning
confidence: 96%
“…It is well known that close to the T g of polymer composites, the molecular chains of the polymer becomes more flexible, thereby gaining mobility. 39 Therefore, the negligible increase in T g of PLA in the PLA-G composite suggests that the incorporation of GF did not sufficiently restrict the mobility of PLA chains in the composite.…”
Section: Dsc Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Tanodekaew et al fabricated PLA/HA scaffolds using additive manufacturing (AM) and found out that the content of HA employed and the size of the pores in the scaffolds influenced directly in the cell growth and differentiation. Akindoyo et al developed composites of PLA/HA using an extruder and injection molding and noticed increase of 20% in tensile and flexural moduli in the samples containing 20% m/m of HA without compatibilizer agents. Similar behavior was observed in PLA/HA casting composites, however, higher contents of HA led to agglomeration effects and consequently to an impairment of the tensile modulus in these composites .…”
Section: Introductionmentioning
confidence: 99%
“…Bioglasses and other bioceramics such as calcium phosphates bond to natural bone and support the proliferation of new cells [2,[13][14][15]. Surface wettability enhances osteoblast adhesion of human cells and also cell proliferation [16][17][18]. The problems associated with the application of metallic implants might be solved by the formation of calcium hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ; CHA) on the surface [19,20].…”
Section: Introductionmentioning
confidence: 99%